On Specific Aesthetic Features of the Plotless “Deviant” Texts in Chronicles - Olga A. Tufanova (Studia Litterarum)
The aesthetic specific of the plotless “deviant” texts in chronicles is rooted in the fact that a detailed or brief account of abnormal and/or extraordinary behaviour of their characters appears in the form of enumerating odd actions, in most cases not connected by cause-and-effect relationship, but directly dependent on the initial event which provoked the manifestation of deviancy. As a rule, such deviant acts are committed in connection with a particular circumstance, such as a fest, an unusual event, a mysterious natural phenomenon, or a natural disaster. The analysis of the plotless narrative about the sorrowful events of 1230–1231 in Novgorod (Novgorod Fourth Chronicle, under 6738), the story about the celestial apparition in Kyiv (Patriarchal or Nikon Chronicle, under 6738), and the Epistle of Hegumen Pamphil (Pskov First Chronicle, under 7013) demonstrates that such plotless “deviant” texts capture both negative and positive deviation in people’s behaviour, as well as in the tradition of narrating various events. Such texts also feature a three-component structure, similar to the plot-driven narrative. However, deviant behaviour is not a trait of human character and way of thinking in the plotless “deviant” texts — it is always caused by a specific circumstance or event and is temporary, although it can be repeated if connected with the ritual aspect of life. Finally, due to their narrative specific, lists of deviant acts primarily refer to mass manifestations of deviant behaviour, as opposed to the plot-driven “deviant” texts, which may focus on a single protagonist.